Дослідження впливу термічної обробки пружино-ресорної сталі 60С2А на структуру та властивості - Яременко, Олександр Юрійович (Харківський національний автомобільно-дорожній університет, 2025)
Object of research – processes of structure formation and formation of steels under the influence of heat treatment. Purpose of the work – to establish the features of the influence of heat treatment on the structure and properties of low-alloy high-quality structural steel. Research methods – information analysis, spectral analysis, optical microscopy, mechanical testing. The qualification work assessed the impact of heat treatment on the structure and properties of spring steel grade 60S2А. During the implementation works conducted research with using the following methods: optical microscopy, mechanical tests (hardness determination) according to standard methods. Received results analysis about influence thermal processing on the structure and hardness indicators of alloyed spring steel allowed us to develop recommendations for heat treatment regimes that are guaranteed to provide sufficient strength (hardness), high dispersion and uniformity of the structure, decarburization within acceptable limits, and the absence of cracking due to high thermal stresses.
Keywords: alloy steel; chemical composition; heat treatment; spectral analysis; mechanical properties; structure; thermostatic resistance